BIOCHEMICAL MARKERS OF ENDOTHELIAL DYSFUNCTION IN INDIVIDUALS WITH BURDEN HYPERTENSION HEREDITY AND PATIENTS WITH STAGE II HYPERTENSION - Kuzminova, N.V.; Romanova, V.O.; Ivankova, A.V.; Lozynskyi, S.E.; Kniazkova, I.I.; Savytska, O.O.; Burdeina, L.V. (World of Medicine and Biology, 2025)
The article presents the results of a study of the levels of biochemical markers of endothelial dysfunction in healthy individuals with a burdened heredity for arterial hypertension and patients with stage II hypertension. The state of vascular endothelium was studied by the levels of NO-synthesizing system (total, inducible and endothelial NO-synthase), the content of stable NO metabolites – S-nitrosothiols, the level of vasoconstrictor endothelin-1 and the activity of von Willebrand factor. It was noted that endothelial dysfunction develops in the serum of healthy individuals with a burdened heredity for hypertension, as evidenced by an increase in the vasoconstrictor and thrombogenic potential of the vascular endothelium, which is also observed in patients with stage II hypertension. Thus, in both groups of subjects, a significant increase in the activity of all types of NO-synthases (total, inducible and endothelial), von Willebrand factor activity and endothelin-1 levels, as well as a decrease in S-nitrosothiol levels (p